DAMPAK PUTUSAN MAHKAMAH KONSTITUSI NO. 46 PUU-VIII / 2010 TENTANG KEABSAHAN STATUS ANAK DI LUAR NIKAH PERSPEKTIF HUKUM PERDATA ISLAM - Yulia Yulia (Al-Bayyinah, 2018)
The view of Islamic Civil Law on the Validity of the position of Children Outside Marriage, is divided into two topics. First, children born from religious marriages are legitimate, but are not recorded in the Marriage Registration Officer and children born from legal marriages, both religiously and legally positive. Both of them have civil relations with their parents. After the Constitutional Court ruling. Second, the child born from the result of adultery only gets legal protection from the decision of the Constitutional Court, namely in terms of maintenance, protection and livelihood until he is an adult. Not in terms of nasab relations with his father not even getting inheritance rights. The decision of the Constitutional Court can be understood as a general rule of law (lex generalis), while the Marriage Law and Compilation of Islamic Law (KHI) are understood as special legal rules (lex specialis) which have more detailed rules than the Constitutional Court ruling, meaning the decision of the Constitutional Court does not immediately abolish article 2 paragraph 2 of the Marriage Law concerning the recording of marriages. So that the decision avoids the interpretation of legalization of adultery.